Manifiesto Liminar celebrates a century: political action and rebellion in defense of the Colombian University - Acevedo Tarazona, Álvaro; Correa Lugos, Andrés David (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2018)
The objective of this reflection article is to analyze the impact that the Manifesto Liminar has on the political and social actions of the university movements in Colombia. University students’ speech propose rebellion as the agglutinating spirit that justifies their collective actions; this vision, shared by the youth of Córdoba, strongly suggest a connection between both movements. This article is derived from a research project that uses a qualitative methodology with an interpretive approach. Primary sources such as the press with semi-structured interviews and historiographic balances are triangulated. Finally, it is stated that the "identity" generated in the midst of rebellion and collective actions in the 1960s and 1970s underwent a transformation in the 1980s to reach the peak of its languor, when the same speech of revolution is adapted by the system during the neoliberal reforms.